The puzzling co-existence of electoral democracy and illegal campaign financing in India - Mitra, Subrata Kumar; Pohlmann, Markus; Hauck, Laura (Journal of Self-Regulation and Regulation, 2019)
Free and fair electi ons and legal campaign funding are the sine qua non of a functioning democracy. The co-existence of a vibrant, resilient democracy and illegal campaign financing in India is puzzling. Based on the case of India, we provide a general explanation for the coincidence of these two normatively discordant elements. We draw on Niklas Luhmann’ concept of ‘useful illegality’ to show how material incentives might actually have contributed to the enhancement of participation in general elections. James Coleman’s principal-agent theory helps us show how the principal (the electorate) selects candidates as agents when they are convinced of their capacity to deliver the benefits they expect. We combine these ideas to cast electoral choice as a rational process whereby candidates and voters are able to communicate, and rationally transact the game of popular elections. Thus, what might come across as illegal campaign and party financing from a normative perspective, is not just a deviance from normative and legal rules. It might actually have been functi onal for initiating and subsequently, sustaining a vibrant democracy in a post-colonial state that began its electoral journey with great social inequality, poverty and illiteracy.